A Comparative Study of the Effect of Sutureless Versus Multiple Sutures Technique on Complications following Third Molar Surgery in Nepalese Subpopulation. (11th February 2020) - Mahat, Arun Kr.; Yadav, Ram; Yadav, Anjani Kr.; Acharya, Pradeep; Dongol, Ashok; Sagtani, Alok; Jaisani, Mehul R.
Abstract : Objective . To compare the effect of sutureless versus multiple sutures technique on postoperative variables such as pain, swelling, and trismus after surgical removal of the third molar in Nepalese subpopulation. Materials and Methods . Forty-eight patients were equally grouped into multiple sutures (group 1) and sutureless (group 2) groups using a computer-generated random table. The same operator performed all the surgical procedures. Postoperative variables such as pain, swelling, and trismus were measured by a single concealed observer using a 10 cm Numerical Rating Scale (NRS), flexible plastic measuring tape, and vernier caliper preoperatively and on 1 st, 2 nd, and 7 th postoperative days. Results . This study showed significantly more swelling measured from the gonion to lateral canthus in group 1 than in group 2 on all postoperative periods (P < 0.05 ). The mean NRS score was significantly higher in group 1 on the 1 st postoperative day (P = 0.01 ). Though mean duration of surgery, swelling as measured from tragus to commissure, trismus, NRS score except on the 1 st postoperative day, total number of analgesics consumed, and complications were noted more in the multiple sutures group, the difference was not statistically significant. Conclusion . Our results support the use of sutureless technique after third molar surgery to minimize postoperative morbidity and the overall operative time and reduce the cost within the Nepalese subpopulation.